(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs), specifically UKM Kemuning Mandiri, significantly contribute to Indonesia’s economic growth but face critical challenges in financial management, including limited accounting knowledge and inadequate use of digital technologies. This community service research aimed to enhance SMEs’ understanding and skills in digital-based financial management using Google Workspace technology. The methods implemented involved structured needs assessments, socialization sessions, intensive training workshops, continuous mentoring support, and evaluation stages to measure effectiveness. Training covered fundamental accounting practices, digital financial reporting through Google Sheets, and leveraging collaborative features of Google Workspace. Results demonstrated substantial improvements: participants’ understanding of accounting principles increased from 30% to 85%, proficiency with Google Sheets rose from 10% to 80%, and financial transparency improved from 20% to 75%. Sustainability measures, including regular discussion forums and continued university support, were established to ensure ongoing application of these skills. The study concluded that the targeted training and mentoring effectively enhanced operational efficiency, accuracy, and transparency in financial management, significantly strengthening SMEs’ competitiveness and sustainability. Recommendations include ongoing technological capacity-building and fostering collaborative partnerships to support continued SME digital transformation.